2022
DOI: 10.24095/hpcdp.42.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Timing of sedentary behaviour and access to sedentary activities in the bedroom and their association with sleep quality and duration in children and youth: a systematic review

Abstract: Background The purpose of this study was to systematically review the relationship between the timing of sedentary behaviours and access to sedentary activities in the bedroom with sleep duration and quality in children and youth. A secondary purpose was to examine whether these relationships differ when comparing screen-based and non-screen-based sedentary activities. Methods We searched four databases for peer-reviewed studies published between 1 January 2010 and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
0
12
0
5
Order By: Relevance
“…Another limitation is that our measure of recreational screen time did not ask adolescents if they consulted screens within 1 h of bedtime while this is also detrimental to adolescents’ sleep [ 22 ]. Timing (i.e., daytime vs. evening) of screen time can have an impact on adolescents’ sleep quality and duration [ 48 ]. Finally, other behavioral variables could affect adolescents’ sleep quality as well, such as caffeine consumption before bedtime [ 29 ].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Another limitation is that our measure of recreational screen time did not ask adolescents if they consulted screens within 1 h of bedtime while this is also detrimental to adolescents’ sleep [ 22 ]. Timing (i.e., daytime vs. evening) of screen time can have an impact on adolescents’ sleep quality and duration [ 48 ]. Finally, other behavioral variables could affect adolescents’ sleep quality as well, such as caffeine consumption before bedtime [ 29 ].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The results indicated that evening/bedtime screen use was associated with reduced sleep duration and quality. 8 While the quality of evidence in the included studies was generally low, the authors concluded that children and youth should limit screen use before bedtime to improve sleep health. 8 Dutil et al 9 also limited their search to children and youth.…”
Section: Abstract: Movement Behaviours Timing Health Outcomes Adaptat...mentioning
confidence: 99%
“…8 While the quality of evidence in the included studies was generally low, the authors concluded that children and youth should limit screen use before bedtime to improve sleep health. 8 Dutil et al 9 also limited their search to children and youth. The studies included in their systematic review described sleep timing as it related to accidents and injuries, adiposity, cardiometabolic risk factors, cognitive function and academic achievement, eating behaviours, emotional regulation, and quality of life and well-being.…”
Section: Abstract: Movement Behaviours Timing Health Outcomes Adaptat...mentioning
confidence: 99%
See 2 more Smart Citations